2006
DOI: 10.1183/09031936.06.00074605
|View full text |Cite
|
Sign up to set email alerts
|

The effect ofPseudomonas aeruginosaon pulmonary function in patients with bronchiectasis

Abstract: Bronchiectasis patients are susceptible to infection with Pseudomonas aeruginosa. Isolation is associated with increased severity of disease, greater airflow obstruction and poorer quality of life. It is not known whether infection by P. aeruginosa is a marker of disease severity or contributes to disease progression.Consecutive non-cystic fibrosis adult bronchiectasis outpatients (n5163) with multiple sputum cultures and follow-up pulmonary function tests were designated, according to isolation of P. aerugino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
102
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 27 publications
15
102
2
4
Order By: Relevance
“…In this meta-analysis, we found that the presence of bronchiectasis in COPD patients was also related to isolation of PPMs and poor lung function. Chronic bacterial infection, especially by P. aeruginosa, was associated with more advanced disease and mortality in both COPD and bronchiectasis patients [32][33][34][35]. The presence of bacteria in the lower airways in COPD impairs host defense mechanisms, which results in epithelial cell integrity disruption and inflammation, further airway structural damage, which could be the mechanism for longer and more severe COPD exacerbations [19].…”
Section: Discussionmentioning
confidence: 99%
“…In this meta-analysis, we found that the presence of bronchiectasis in COPD patients was also related to isolation of PPMs and poor lung function. Chronic bacterial infection, especially by P. aeruginosa, was associated with more advanced disease and mortality in both COPD and bronchiectasis patients [32][33][34][35]. The presence of bacteria in the lower airways in COPD impairs host defense mechanisms, which results in epithelial cell integrity disruption and inflammation, further airway structural damage, which could be the mechanism for longer and more severe COPD exacerbations [19].…”
Section: Discussionmentioning
confidence: 99%
“…Neither the presence of chronic colonisation by multiresistant Gramnegative bacilli nor the isolation of Staphylococcus aureus, atypical mycobacteria and fungi, presented any significant independent predictive power for mortality. Therefore, it was finally decided to include only chronic colonisation by P. aeruginosa in the score, as this is the only microorganism that has been related in the current literature with an increase in mortality and a poorer functional evolution in patients with non-CF bronchiectasis [5,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Davies et al, [23] PA infection in patients with non-CF bronchiectasis was shown to be a marker of disease severity, but was not linked to an accelerated decline in pulmonary function.…”
Section: Discussionmentioning
confidence: 95%